Gender dimensions in training and development at the information and communication technology sector in Egypt - Khayyat, Rozana Adnan (AUC Knowledge Fountain, 2014)
This study examines women's career potentials at the information and communication technology (ICT) sector in Egypt. Taking a case study approach, the study particularly focuses on female employees' involvement in training and developing activities for skill and capacity building. The findings of this study show that most of the female employees in the case study hold administrative positions. Training activities actually increase the gap between male and female workers, as male workers were allowed more technical and expensive training opportunities than female employees. The interviews also reveal the payment inequality between male and female employees in the case study organization. The study shows that the pressures of scheduling training courses and the heavy daily work demands on female employees all hinder their career growth potentials.